Interstitial ectopic pregnancy rupture at 17 weeks of gestation: A case report and literature review - Vishal Bahall; Wendel Cozier; Petal Latchman; Sarah-Ann Elias; Steven Sankar (Elsevier, 2022)
Interstitial pregnancy is a rare type of ectopic pregnancy that commonly results in uterine rupture and life-threatening haemorrhage. Interstitial ectopic pregnancies are associated with a 2-5% mortality rate and a high risk of uterine rupture before 12 weeks of gestation when compared to tubal pregnancy. Due to the thickness and distensibility of the interstitial segment of the Fallopian tube, ectopic pregnancy in this location attains a considerable size before complications arise. Unfortunately, this clinical entity may prove to be a diagnostic challenge, leading to delays in treatment and significant morbidity and mortality in women of reproductive age. Herein, we report a case of a ruptured interstitial ectopic pregnancy occurring at 17 weeks of gestation that was successfully managed with surgical intervention, after proving to be a diagnostic challenge.